Effect of culture medium and physiological state of the explant on callus formation and development in winter and spring wheat (Triticum aestivum L.) - Fedotov, P. A.; Lyubushkina, I. V. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2025)
Callus cultures have long been used in many works to study physiological processes and the effects of environmental factors on plant organisms. Of great importance, including for agriculture, are the callus cultures of cereals, specifically Triticum aestivum L. (wheat). However, callus induction and its effective growth are complicated by the genetic and physiological characteristics of a particular species or cultivar. In this connection, the study was aimed at examining the growth of callus cultures of winter and spring wheat on different growth media, as well as identifying the optimal medium for callus induction and effective callus growth. As explants, the study used the germs of imbibed and dry seeds. The germ was isolated from the seed and incubated on Murashige and Skoog medium, Gamborg medium, and Chu medium (modified with the microsalts of Blaydes medium) under aseptic conditions. As a growth regulator, the study used 2,4-dichlorophenoxyacetic acid at a concentration of 2.5 mg/L. The germs were cultivated for three weeks at 26 °С in the dark. In order to evaluate the effectiveness of culture media, the callus formation rate and callus biomass growth were recorded. Active callus induction was observed in the culture of dry winter and spring wheat germs on all of the used media. In the case of imbibed germs, the maximum callus formation rate in winter wheat was observed on Murashige and Skoog medium, whereas in spring wheat, it was observed on Gamborg medium. In terms of the callus growth rate, Murashige and Skoog medium and Chu medium were found to be more appropriate for cultivating winter wheat explants, while Gamborg medium showed better results for cultivating spring wheat explants.